Development of Textile and Alcohol Packaging Products: A Case Study of Changhai Village, Pak Ou District, Luang Prabang Province - sengphachanh, Bouasavanh; SENGPHACHANH, Bouasavanh; VONHVILAI, Xaiyaphone; PHONESALY, Naunseng (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study explores the development of fabric and liquor bottle packaging products by integrating local wisdom from the Ban Chang Hai community in Luang Prabang Province. The objective is to create distinctive designs that reflect the community’s contemporary lifestyle and cultural identity. Additionally, the research aims to enhance economic value, promote community-based tourism, and support sustainable local economic development. The study’s target group includes 20 local residents and tourism-related entrepreneurs, along with a sample of tourists who visited the area between 2023 and 2024. Data collection employed qualitative methods such as in-depth interviews, focus group discussions, and field observations to identify existing challenges and development needs in product design. Findings reveal that current community products lack packaging designs that clearly express local identity in terms of style, patterns, and color schemes. Most production still relies on traditional methods, and marketing channels remain limited. Furthermore, there is a lack of storytelling to effectively convey the community’s cultural values and lifestyle to consumers. The study highlights that incorporating local wisdom such as traditional liquor distillation techniques and Saew weaving into product and packaging design can create new market opportunities and significantly increase economic value. Aligning cultural identity with market demands, particularly among tourists, emerges as a key strategy for improving local livelihoods. Moreover, the research identifies that existing tourism models primarily offer short visits with limited engagement, lacking deep knowledge transfer of the community’s rich cultural heritage, authentic way of life, and detailed production processes. Therefore, the study recommends new approaches to product design and tourist activities that provide immersive, participatory experiences. These initiatives are expected to foster meaningful learning, increase the perceived value of local products, generate community income, and contribute to the long-term preservation of local wisdom.